Men's Experiences of Violence in Intimate Relationships - Lien, Marianne Inéz; Lorentzen, Jørgen (Palgrave Studies in Victims and Victimology,, 2019)
"This is an important book on an under-acknowledged issue of great relevance to men's health. By shining a light on these victims hopefully society can open its eyes to their plight and the need for a more informed debate on what happens behind closed doors and the support needs of affected men." (Alan White, Emeritus Professor of Men's Health, Leeds Beckett University, UK; Patron, The Men's Health Forum) "This book is a must read for researchers, practitioners, and policymakers in the field of family violence. Lien and Lorentzen provide an important and compelling addition to the growing body of work that shows just how serious and harmful partner violence can be to male victims and their children. Compelling case studies are complemented by quantitative studies and excellent research to demonstrate how vital it is for the field to learn more about male victims and update our theoretical understanding of partner violence." (Denise A. Hines, Associate Research Professor and Director, Massachusetts Family Impact Seminars, Clark University, USA) This open access book draws on a broad study on violence against men, from both male and female partners in Norway, to contribute to the research on intimate partner violence. It identifies similarities in men's experiences and backgrounds, including in their perceptions of their own victimisation. Marianne Inez Lien and Jørgen Lorentzen argue that the traditional gender power model should be modified and supplemented, and propose that we consider violence in terms of psychological supremacy, rather than in terms of femininity and masculinity. Men's Experiences of Violence in Intimate Relationships will appeal to students and scholars across a range of areas including criminology, sociology and family violence, and gender studies.